DESIGN AND MANUFACTURE OF A FISH PELLET MACHINE WITH A SCREW EXTRUDER METHOD CAPACITY OF BATTER 2.35 TONS/HOUR - N. Nazaruddin; Sulaiman (Jurnal Teknologika, 2020)
The design of this fish pellet production machine is based on the working principle of a screw extruder. The working principle of this screw extruder is used for compaction by pushing the dough in the mold which ultimately results in fish pellets in accordance with the size of the mold hole continuously. Screw extruder is made by cutting the steel plate to form a ring. Then the steel plate is spiral formed by heat treatment and then welded to the screw extruder shaft. A binding pellet machine with screw extruder method has been successfully made with components in the form of hopper, screw extruder, screw cylinder, reducer, motor and mold plate. The screw extruder is capable of delivering the dough material at 2.23 m3/hour with a rotation of 35 rpm with a screw diameter of 6 inch. This fish pellet is driven by an electric motor with 1 HP power. This electric motor will drive the reducer, then turn the screw extruder. This fish pellet production machine has produced a fish pellet production capacity of 2,35 ton/hour